K-State Turfgrass Research 2004 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Turfgrass Research 2004 contains results of projects done by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day at the Rocky Ford Turfgrass Research Center in Manhattan on August 5. The enclosed articles present summaries of research projects have been recently completed, or will be completed in the next year or two. Specifically, this yearʼs report presents summaries of research on environmental stresses, turfgrass establishment and culture, and cultivar evaluations.
Keywords: Turfgrass; Environmental stress; Cultivar evaluations; Bluegrass; Bermudagrass; Creeping Bentgrass; Tall Fescue; Buffalograss; Ryegrass; Zoysiagrass